Analisis Sejarah Perkembangan Mazhab Fiqh dan Pengaruhnya terhadap Hukum Islam Kontemporer - Husnu Shidqiah; Muhammad Husni Abdulah Pakarti; Diana Farid; Husain Husain; Ulummudin Ulummudin; Ais Surasa (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Islamic fiqh is an evolving legal system influenced by the various fiqh madhhabs that have emerged since the early days of Islam. This diversity has contributed significantly to the application of Islamic law in the contemporary world. This study aims to analyze the historical development of the main fiqh madhhabs (Hanafi, Maliki, Shafi'i, and Hanbali) and their influence on the practice of Islamic law in the context of legal pluralism and fiqh reform in Muslim countries. This research uses a historical and analytical approach by examining classical fiqh literature and the development of modern Islamic law. It analyzes fiqh texts, legal decisions, and Islamic legal policies implemented in various Muslim countries. The results show that fiqh madhhabs played an important role in the formation of diverse Islamic legal systems. The influence of these madhhabs can be seen in the application of sharia law in various Muslim countries, despite differences in its recognition and implementation. In addition, the fiqh madhhabs also contribute to the socio-political dynamics in Muslim societies. This study asserts that despite the challenges in adapting fiqh to the modern era, a flexible and inclusive approach to fiqh can be a solution in dealing with global legal issues. Fiqh reforms that take into account the social context and needs of Muslim societies can enhance the relevance and justice of Islamic law in the contemporary era.